Interleukin-6 in Hypothyroidism - Nagila, Amar; Paudel, Khem Raj; Subedi, Bijay (Journal of Manmohan Memorial Institute of Health Sciences, 2024)
Background: Hypothyroidism means that the thyroid gland can’t produce enough thyroid hormones. Interleukin 6 (IL-6) a cytokine of innate immunity is a soluble mediator with a pleotropic effect on inflammation. Interleukin 6 test is helpful to study the hypothyroid status and to assess the adverse effects of hypothyroidism, was not studied in a tertiary care center in Pokhara, Nepal. The aim of this study is to determine the levels of interleukin 6 and to correlate with hypothyroidism. Methodology: This was a hospital based cross-sectional study on 100 hypothyroid patients where samples were collected by convenient sampling from patients visiting the Tertiary care Hospital in Pokhara, Nepal. Thyroid function tests fT3, fT4 and TSH were analyzed by Chemiluminiscence Immunoassay (CLIA) for hypothyroidism. Interleukin 6 test was estimated by Immunofluorescence Assay (IFA). Excel-2010 and SPSS V 16.0 were used for data analysis. Result: Among the total hypothyroid population, 83(83.0%) were subclinical and 17(17.0%) were overt cases. The 31(31.0%) of the total population has increased level of IL-6 and 69(69.0%) were normal. In this study, out of the 17% overt cases IL-6 was increased in 82.35 % cases and 17.65% of them found normal. In case of 83% subclinical hypothyroidism, IL-6 was increased in only 20.48% of cases and 79.52% of them found normal. There was a significant association between inflammatory status and hypothyroid status. IL-6 was significantly correlated with fT3 (r= -0.485, p<0.01fT4 (r= -0.521, p<0.01) and TSH (r= 0.547, p<0.01). Conclusion: This study suggests that hypothyroid patients may have increased level of Interleukin 6. The frequency of inflammatory cases and severity of inflammation have been increased when cases worsen from subclinical to overt. Therefore, hypothyroidism must be treated early to avoid the consequences of inflammation. Keywords: Hypothyroidism, Interleukin-6, fT3, fT4